2023
DOI: 10.1097/qad.0000000000003675
|View full text |Cite
|
Sign up to set email alerts
|

Vascular injury markers associated with cognitive impairment in people with HIV on suppressive antiretroviral therapy

Debjani Guha,
Vikas Misra,
Jun Yin
et al.

Abstract: Objective: Human immunodeficiency virus (HIV)-associated neurocognitive disorders (HAND) remain prevalent despite viral suppression on antiretroviral therapy (ART). Vascular disease contributes to HAND, but peripheral markers that distinguish vascular cognitive impairment (VCI) from HIV-related etiologies remain unclear. Design: Cross-sectional study of vascular injury, inflammation, and central nervous system (CNS) injury markers in relation to HAND. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…We found that soluble plasma vascular injury markers (ICAM-1, VCAM-1, and CRP) were associated with HAND, similar to findings in our recent study [ 55 ]. However, EV-associated forms of these markers did not show significant associations with HAND.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that soluble plasma vascular injury markers (ICAM-1, VCAM-1, and CRP) were associated with HAND, similar to findings in our recent study [ 55 ]. However, EV-associated forms of these markers did not show significant associations with HAND.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent study, we showed that soluble forms of vascular injury markers are increased in PWH with HAND compared with no HAND [ 55 ]. To determine if EV-associated forms of these markers have stronger associations with HAND compared to soluble forms, we examined the association of plasma EV-associated vascular injury markers (ICAM-1, VCAM-1, CRP) with HIV status, HAND, and vascular disease ( Supplemental Digital Content S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although CSF NFL, GFAP, and YKL-40 levels were not significantly different between PWH with or without asymptomatic CSF viral escape, CSF YKL-40 correlated positively with CSF IL-1β, IFN-γ, IP-10, and NFL and negatively with neurocognitive T scores. Previous studies have suggested that CSF YKL-40 is associated with increased plasma and CSF HIV/SIV RNA, HIV/SIV encephalitis, and markers of axonal injury [ 19 , 21 , 22 , 48 , 51 , 52 ]. CSF YKL-40 is a biomarker of glial activation associated with neuroinflammation [ 19 , 21 , 53 ] that is produced by CNS macrophages, microglia, and astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…CSF and plasma albumin levels were measured using the BCG albumin assay kit (Thermo Fisher Scientific, Waltham, MA, USA), as described [ 48 ]. The CSF-plasma albumin ratio was calculated as an indirect indicator of blood-brain barrier integrity.…”
Section: Methodsmentioning
confidence: 99%
“…The decrease in mitochondrial DNA copy number in late-passage human aortic endothelial cells and the elevation of senescence-associated β-galactosidase accumulation have been observed in PLWH dysfunction and vascular injury; together with ICAM-1, it has been used in many clinical studies to estimate the risk of CVD [137]. It has been reported that the expression of adhesion molecules in PLWH is significantly higher than in the general population [138].…”
Section: Metabolic Effects Of Antiretroviral Therapymentioning
confidence: 99%